CRITICAL ANALYSIS OF THE INFLUENCE OF BOYS' LOVE FILMS ON GENERATION Z'S PERSPECTIVE REGARDING LGBT (LESBIAN, GAY, BISEXUAL, AND TRANSGENDER) - Iis Juniati; Dinda Citra Dewi (Adisam Publisher, 2025)
Boys' Love (BL) films serve as an effective medium for increasing tolerance and understanding towards the LGBT community. The current easy access through various digital media platforms is a supporting factor. The proliferation of BL content films has now